Exit, Control, and Politics: Structural Power and Corporate Governance under Asset Manager Capitalism*. (December 2022) - Braun, Benjamin
The power of finance vis-à-vis the nonfinancial sector is changing. Macroeconomic developments and financial innovations have reduced financial actors' exit options, thus diminishing exit-based structural power. At the same time, shareholdings have become more concentrated in the hands of large asset managers, thus increasing control-based power. This article documents these trends, before examining whether asset managers wield their power and why, despite being universal shareholders, they have not steered corporate behavior toward decarbonization. Rather than assuming orderly, good-faith interactions between shareholders and managers, this article argues that in the United States today, political considerations govern the use of control-based power. Asset managers' corporate governance policies are subservient to the—increasingly inconsistent—goals of maximizing assets under management while avoiding regulatory backlash. Unlike exit-based power, control-based power is constrained by being highly visible and, therefore, easily politicized.